2006
DOI: 10.1128/mcb.02053-05
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mating and Filamentation Genes by Two Distinct Ste12 Complexes in Saccharomyces cerevisiae

Abstract: The Saccharomyces cerevisiae transcription factor Ste12 controls two distinct developmental programs of mating and filamentation. Ste12 activity is regulated by Fus3 and Kss1 mitogen-activated protein kinases through two Ste12 inhibitors, Dig1 and Dig2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
168
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(175 citation statements)
references
References 52 publications
7
168
0
Order By: Relevance
“…Deletion of Kss1 did not alter the ability of ubp3⌬ cells to invade solid agar, in agreement with previous observations (44). In particular, deletion of Kss1 is thought to promote invasive growth by relieving Dig1/ Dig2-mediated inhibition of Ste12 and Tec1, which mediate transcription of genes containing filamentous response elements (43)(44)(45).…”
Section: Cdc4 Promotes Activation Of Fus3 and Ubp3supporting
confidence: 78%
“…Deletion of Kss1 did not alter the ability of ubp3⌬ cells to invade solid agar, in agreement with previous observations (44). In particular, deletion of Kss1 is thought to promote invasive growth by relieving Dig1/ Dig2-mediated inhibition of Ste12 and Tec1, which mediate transcription of genes containing filamentous response elements (43)(44)(45).…”
Section: Cdc4 Promotes Activation Of Fus3 and Ubp3supporting
confidence: 78%
“…This is the case for Ste12 and Tec1, TFs involved in two distinct developmental programs: mating and filamentation (Chou et al 2006). Chou and colleagues have shown that during mating-a process induced by treatment with alpha pheromone-promoters of mating genes are bound mostly by Ste12-Dig1-Dig2, but also by the Ste12-Tec1-Dig1 complex, with Ste12 binding DNA directly.…”
Section: Sfp1 and Fhl1 Are Two Factors That May Bind Dna Indirectly mentioning
confidence: 99%
“…Chou and colleagues have shown that during mating-a process induced by treatment with alpha pheromone-promoters of mating genes are bound mostly by Ste12-Dig1-Dig2, but also by the Ste12-Tec1-Dig1 complex, with Ste12 binding DNA directly. During filamentation-a program induced by butanol treatmentpromoters of most filamentation genes are bound by the Tec1-Ste12-Dig1 complex, with Tec1 binding DNA directly (Chou et al 2006).…”
Section: Sfp1 and Fhl1 Are Two Factors That May Bind Dna Indirectly mentioning
confidence: 99%
See 1 more Smart Citation
“…A block of Tec1-degradation during mating not only interferes with down-regulation of CLN1 expression, but also with an efficient G1 arrest (Brückner et al 2004). In addition, Tec1 is stabilized by complex formation with Ste12 by a mechanism that is independent of the CPD, but involves the C-terminal part of Tec1 (Chou et al 2006;Heise et al 2010).…”
mentioning
confidence: 99%